Design for sustainability a practical approach - Bhamra, Tracy; Lofthouse, Vicky (Design for social responsibility., 2007)
Presents a practical approach to design which focuses on the challenges and issues faced by those designing consumer products in the 21st Century. This book answer questions such as: What is sustainable product development and why is it important? What are the main drivers of sustainable product development?